The Effect of Giving D-Galactose as an Aging Inducer on Body Weight, Glucose Levels and Interleukin-6 Levels in Wistar Rats - Gama, Arlina Wiyata; Akib, Rahmawati; Khaera, Ummul (PSPP JOURNALS, 2025)
Aging is a complex biological process characterized by a decline in physiological functions and an increased susceptibility to chronic diseases. D-galactose, although a naturally occurring monosaccharide, can induce aging when administered in high doses by increasing oxidative stress and inflammation, as indicated by elevated levels of reactive oxygen species (ROS) and interleukin-6 (IL-6). This study aimed to analyze the changes in body weight, blood glucose levels, and IL-6 levels in Wistar rats following D-galactose administration, with the goal of gaining insights into aging mechanisms and exploring potential therapeutic targets for age-related diseases. This was an experimental study using a pre- and post-test design, involving 20 male Wistar rats divided into two groups: a treatment group that received 150 mg/kgBW of D-galactose and a control group that received 0.9% NaCl, both for a duration of six weeks. The study was conducted at the PSPD Research Laboratory, Faculty of Medicine and Health Sciences, UIN Alauddin Makassar, from August to October 2024. Body weight, fasting blood glucose, and serum IL-6 levels were measured weekly using ELISA and a glucometer. Variables analyzed included body weight, glucose levels, and IL-6 levels, with controlled variables such as age, sex, strain, feed, water, and housing conditions. Data were analyzed using an independent t-test with a significance level of p < 0.05. Although changes were observed in all variables, the administration of D-galactose did not result in statistically significant differences in body weight or blood glucose levels between the treatment and control groups. These findings suggest that the aging process induced by D-galactose may involve more complex mechanisms and require further investigation to fully understand its effects and implications for human health.